(2E, 6E)‐2, 6‐Bis(organylchalogenylmethylidene) substituted 1, 4‐dithiane 1, 1, 4, 4‐tetraoxides and N‐organyl thiomorpholine 1‐oxides as new S‐oxide derivatives of bis(2‐organylchalcogenylvinyl) sulfides. Issue 2 (10th June 2018) - Martynov, Alexander V.; Makhaeva, Nataliya A.; Amosova, Svetlana V.
Abstract: It is shown that (2 E, 6 E )‐2, 6‐bis(chloromethylidene)‐ N ‐organyl thiomorpholine 1‐oxides and (2 E, 6 E )‐2, 6‐bis(chloromethylidene)‐1, 4‐dithiane 1, 1, 4, 4‐tetraoxides, unlike unoxidized analogs, (2 E, 6 E )‐2, 6‐bis(chloromethylidene)‐ N ‐organyl thiomorpholines, and (2 E, 6 E )‐2, 6‐bis(chloromethylidene)‐1, 4‐dithiane, easily undergo stereoselective nucleophilic vinylic substitution reactions with such chalcogen‐containing nucleophiles as sodium 1‐butanethiolate, arenethiolates, and benzeneselenolate to afford previously unknown (2 E, 6 E )‐2, 6‐bis(organylchalogenylmethylidene)‐ N ‐organyl thiomorpholine 1‐oxides and (2 E, 6 E )‐2, 6‐bis(organylchalogenylmethylidene)‐1, 4‐dithiane 1, 1, 4, 4‐tetraoxides in high yields. The structures of the heterocycles formed have been confirmed by 1 H, 13 C NMR, and mass spectrometry data.